Acquisition of genetic mutations in Group A Streptococci at infection site and subsequent systemic dissemination of the mutants with lethal mutations in a streptococcal toxic shock syndrome mouse model. (June 2020) - Otsuji, Ken; Fukuda, Kazumasa; Maruoka, Tsukasa; Ogawa, Midori; Saito, Mitsumasa
Abstract: Streptococcal toxic shock syndrome (STSS) is caused mainly by Streptococcus pyogenes (Group A Streptococci, GAS), and it has a fatality rate of 25%. Mutations in CsrRS and RopB, which suppress the transcription of many virulence factors, were recently found in clinical isolates from STSS patients, but it is not fully understood when and where GAS acquires the mutations in the host. To resolve this question, we used our mouse model of human STSS to recover GAS strains from injections sites, spleens and blood of moribund mice with STSS-like symptoms, and analyzed the sequence of the covR / covS genes and ropB gene that encode CsrRS and RopB. Fifteen out of twenty mice that were inoculated transdermally into muscles with GAS organisms became moribund with STSS-like symptoms after more than 20 days after inoculation. We found that all the disseminated GAS strains recovered from the blood and spleens of the moribund mice had mutations in either the covR genes or the covS genes. The mutation sites in the GAS strains recovered from the blood and spleen were identical in each mouse, whereas the strains recovered from the muscles included a mix of disseminated strains, other mutant strains, and the parent strain. The mutant strains killed mice significantly earlier than the parent strain. Our data indicated that GAS organisms remained at the injection site, and various mutants appeared there, among which the strain that acquires the mutation in the covR/S gene is expected to overexpress various virulence factors simultaneously and cause systemic infection such as STSS. Highlights: CsrRS and RopB mutation in S. pyogenes (GAS) are associated with invasive infection . Mutations of CsrRS and RopB in GAS were analyzed using our STSS model mice. Various mutants including invasive mutant appeared in the injection site. Disseminated strains recovered from blood and spleens were identical in each mouse. Invasive mutants appeared at the injection site disseminates and leads mice dead.